(untitled) (Swiss Medical Weekly, 2024)
Cigarette smoking remains an enormous public health problem causing millions of preventable deaths annually worldwide. Although safe and efficient smoking cessation pharmacotherapies such as nicotine replacement products and the medications varenicline and bupropion are available, long-term abstinence rates remain low and new approaches to help smokers successfully quit smoking are needed. In recent years, electronic nicotine delivery systems such as e-cigarettes and heated-tobacco products, and novel smokeless nicotine delivery products like nicotine pouches have gained widespread popularity. These products can deliver nicotine without combustion of tobacco and might thus present an alternative to the currently available smoking cessation methods if they prove able to help smokers quit smoking conventional cigarettes while decreasing their exposure to toxicants. In this narrative review, we provide a summary of the characteristics of these novel nicotine delivery products and the available data regarding their efficacy as smoking cessation tools and safety profile with a focus on the current situation in Switzerland.